JENA ROMANTICISM AND NATIONAL AND CULTURAL IDENTITY - Yulian E. Grinivetskiy (Вестник Северо-Кавказского федерального университета)
This article discusses features of the reflection of national and cultural identity in Jena Romanticism. Generalized orientation literary movement as an expression of the philosophical, national and cultural consciousness.